Letter regarding "Association between triglyceride-glucose (TyG) index and risk of depression in middle-aged and elderly Chinese adults: Evidence from a large national cohort study." - Seshadri Reddy Varikasuvu; Subodh Kumar (Biomolecules & Biomedicine)
This correspondence addresses the recent study by Xu et al. examining the relationship between the triglyceride-glucose (TyG) index and depression in older Chinese adults. The study's identification of a J-shaped association between TyG levels and depressive symptoms adds meaningful insight into the connection between metabolic health and mental well-being. However, when considered alongside other findings, including those using combined indices such as TyG-BMI and TyG-WHtR, the results suggest that a broader, multidimensional approach may offer greater predictive value. Supporting studies have linked these composite measures not only to depression but also to wider metabolic and cardiovascular risks. Additionally, other reviews highlight the potential link between TyG and more severe psychiatric conditions. The letter emphasizes the need for further research, especially longitudinal and interventional studies, to clarify causal relationships and explore whether improving metabolic health can help prevent or reduce depressive symptoms. The authors encourage continued exploration of metabolic indicators not just as risk markers but as possible targets for intervention.